Temporality of Suspension - Tuma, Lucie; Kumār, Kiran (The Nordic Journal of Aesthetics, 2022)
NOTE FROM THE AUTHORS The context of our co-authored contribution to the ‘Aesthetic Relations’ conference-publication is a performance devised by Lucie in 2020 to which she invited Kiraṇ as a collaborator. Due to international travel restrictions however, our physical co-pres-ence in a studio and on stage remained suspended throughout that year. Our exchanges nevertheless continued in adaptive turns both before and after that performance. It is this condition of, at once, compromised yet consistent relation with each other that we refer to as ‘suspension’. For us this suspension was at first admittedly a source of disruption, even anxiety of interrupting our artistic flow. Yet there came a point during the year when this swelling tension ruptured, and a strange ease set in. Nothing had changed on the surface (travel restrictions were only extended), yet something had shifted under our skins. While still physically across continents, our online presentation at the conference was a joint essay at articulating, both textually and performatively, the unassuming complexity of this thing that is suspension. By the time of this publication in 2022, we have somewhat broken this suspension by physically meeting in Switzerland in August 2021. As such we have decided not to edit the text that was performed at the conference back in January 2021, and only append it with this contextual note. Here we must add that the text in one of the sections to follow (which begins with “Please turn your head to your left..”) is intended as a score for action. Originally spoken in our voices, we now ask you to invite another person to read this section aloud to you at an unhurried pace, while you respond to the text’s suggestions. As for us, we continue our collabora-tive artistic research of working in and with suspension as artistic strategy through our ongoing exchanges and upcoming projects.